2003
DOI: 10.1306/111302730367
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Geomorphology and Stratigraphy of Depositional Elements in Deep-Water Settings

Abstract: This PDF Content is made available by SEPM-Society for Sedimentary Geology for non-commercial use. This file does contain security features to prevent changing, copying items or printing the document. Additional restrictions and information can be found below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
818
1
14

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 948 publications
(864 citation statements)
references
References 75 publications
31
818
1
14
Order By: Relevance
“…The lateral migration of sandstone facies within and among inferred channel geometries suggests some degree of sinuosity of the channel systems. Sinuous and laterally accreting channels tend to form as a result of sediment accumulation at inner and outer channel bends, unlike fluvial systems that consistently erode at outer bends and deposit sediments on inner channel bends (Posamentier & Kolla, 2003;Kane et al, 2008;Janocko et al, 2013). The variable degree of deposition and bypass in submarine systems allows for more stable channel geometries than in the fluvial counterpart.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The lateral migration of sandstone facies within and among inferred channel geometries suggests some degree of sinuosity of the channel systems. Sinuous and laterally accreting channels tend to form as a result of sediment accumulation at inner and outer channel bends, unlike fluvial systems that consistently erode at outer bends and deposit sediments on inner channel bends (Posamentier & Kolla, 2003;Kane et al, 2008;Janocko et al, 2013). The variable degree of deposition and bypass in submarine systems allows for more stable channel geometries than in the fluvial counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, general consensus that the axial part of the channel will be a zone dominated by coarse-grained sediment bypass lags (Fig. 4B), and that lateral migration will still occur (e.g., Abreu et al, 2003;Posamentier & Kolla, 2003). Because of the asymmetry in channel cross-section created by the variable flows, instability and slumping is likely to occur at channel margins when the deepest part of the channel is shifted towards either of the channel margins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…debris flows, slides, slumps) (Dott, 1963;Nardin et al, 1979;Hampton et al, 1996;Mulder and Cochonat, 1996;Moscardelli and Wood, 2008) ( Figure 1.1). MTCs are volumetrically important in modern and ancient deepwater basins (Posamentier and Kolla, 2003) and have a significant interplay with turbidites (Pickering and Corregidor, 2005;Nelson et al, 2011;Ortiz-Karpf et al, 2015)-a typical reservoirquality deposit in petroleum exploration. Although, for obvious industrial reasons, turbidites have received the most attention during the past decades, the more recent acquisition of high-resolution three-dimensional (3-D) seismic data has shown that many slope and abyssal systems comprise a very significant portion of MTCs.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%